Genetic And Non-Genetic Factors Affecting Breeding Efficiency In Malvi Cows - Tomar, S.S.; Sharma, Harish; Singh , Ashok (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Effects of period and season of first calving and inbreeding on breeding efficiency by Wilcox (BEW) and Tomar (BET) Methods were studied on 403 Malvi cows maintained at the Government Cattle Breeding Farm, Agar, District Shajapur (M.P.). The least squares means of BEW and BET were found to be 88.04±1.52 and 76.83±0.89 per cent, respectively. Both the breeding efficiency were significantly (P<0.01) affected by the period of first calving and inbreeding. The effect of season of first calving was non-significant. From the results it could be inferred that inbreeding has adverse effect on breeding efficiency as inbred cows had significantly lower breeding efficiency in comparison to non-inbred cows.